Effective weed management strategy for maize (Zea mays) under rainfed condition of southern Rajasthan - Hargilas, Hargilas (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted during the rainy season of 2015 and 2016 at Agricultural Research Station (MPUAT), Banswara, Rajasthan to find out effective weed management strategy for enhancing productivity and economic return of maize (Zea mays L.) under rain-fed condition of southern Rajasthan. Ten treatment combinations of pre-emergence (atrazine and pendimethalin), post-emergence (2,4-D amine, halosulfuron and tembotrione) herbicides with weed free and weedy check were laid out in randomized block design with three replications. The result revealed that application of atrazine 50WP @1.5 kg/ha PE fb tembotrione 42SC @286 g/ha POE at 25 DAS significantly reduced weed density and weed dry weight with increased weed control efficiency and weed control index at 50 DAS as compared to other herbicidal treatments. The weed free treatment gave significantly higher plant height, yield attributes, grain yield (6.31 and 6.86 t/ha) and stover yield (6.87 and 8.15 t/ha), HEI (67.51%) and gross return (₹ 88363/ha) followed by application of atrazine as PE fb tembotrione as POE at 25 DAS over rest of the treatments. While, net return (₹ 55498/ha) and B:C ratio (2.05) recorded highest with application of atrazine PE fb tembotrione POE at 25 DAS than weed free and rest of the treatments. Hence, sequential application of atrazine 50WP @1.5 kg/ha PE fb tembotrione 42SC @286 g/ha POE at 25 DAS may be recommended for enhancing productivity and economic return through effective weed management in maize under rainfed condition of southern Rajasthan.